2020
DOI: 10.21203/rs.3.rs-41855/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Need for Additional Mental Health Support for Women in the Postpartum Period in the Times of Epidemic Crisis

Abstract: Background: This study aimed to identify possible intensification of mental health difficulties among women seeking support in the postpartum period during the epidemic state in Poland. We assumed that the epidemic crisis, social isolation and restrictions in hospitals which affect pregnant and postpartum women - lack of family labours, lack of the possibility to be with the newborn when he/she is hospitalized, may increase fear and reduce psychosocial resources of women, hinder their normal process of transit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(28 reference statements)
1
4
0
1
Order By: Relevance
“…However, our results indicate that these worries seem to have been intensified during the lockdown. Furthermore, we found that feelings of loneliness were described as more pronounced during the lockdown; this has been confirmed by other studies investigating mental health among women during times with COVID-19 [15,20,34]. Taken together, these findings warrant attention to mental health in women, including those with recent GDM, during COVID-19, and to support a focus on motherhood adaptation and the infant's social progression as common worries in the infant period.…”
Section: Worries and Difficulties During The Covid-19 Lockdownsupporting
confidence: 87%
“…However, our results indicate that these worries seem to have been intensified during the lockdown. Furthermore, we found that feelings of loneliness were described as more pronounced during the lockdown; this has been confirmed by other studies investigating mental health among women during times with COVID-19 [15,20,34]. Taken together, these findings warrant attention to mental health in women, including those with recent GDM, during COVID-19, and to support a focus on motherhood adaptation and the infant's social progression as common worries in the infant period.…”
Section: Worries and Difficulties During The Covid-19 Lockdownsupporting
confidence: 87%
“…Our findings indicate that the COVID‐19 pandemic and the implementation of the restrictive measures had impact on the daily lives and economic statuses of postpartum mothers, which might have led to decreased social interactions and social activities, as well as income instability, all of which might have caused the postpartum mothers to receive less social support and experience more mental health problems. Similarly, Chrzan‐Dętkoś et al (2021) revealed that the situation of the COVID‐19 pandemic and restrictive measures might be an additional risk factor for increasing the prevalence and severity of PPD (Chrzan‐Dętkoś et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum women have identified four types of desired social support after delivery such as informational support, emotional support, shared experiences with assistance and instrumental support (Slomian et al, 2019). During the COVID‐19 pandemic, postpartum women have had increasing need for additional social support after childbirth (Chrzan‐Dętkoś et al, 2021). However, the pandemic of COVID‐19 has impact on received social support.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos destacam que as puérperas passam por importantes mudanças nas dinâmicas familiares, trabalho, vida social, percepção da autoimagem, admiração do trabalho doméstico, na percepção de felicidade e na adaptação com a rotina de amamentação, e em outras variáveis que podem impactar na qualidade de vida geral (Castiglioni et al, 2020;Cetisli, Arkan, & Top, 2018;Chrzan-Dętkoś, Walczak-Kozłowska, & Lipowska, 2021;Meireles et al, 2020).…”
Section: Introductionunclassified